The impact of information technology on accounting systems towards SME performance in Malaysia - Abdullah, Shamsul Nahar; Aziz, Azbariyah Abdul; Saifulazri, Batrisyia Qysara (Journal of Social Economics Research, 2023)
This study seeks to investigate the impact of accounting information systems on the performance of small and medium-sized enterprises (SMEs) in Malaysia. SMEs were the focus of this study due to their importance to the economy. The features of an accounting system, namely accuracy, efficiency, reliability, data quality, and ease of use, were tested against the performance of a sample of SMEs that implemented an Accounting Information System (AIS) in their companies. A closed-ended questionnaire consisting of a five-point Likert scale was used to gather the data. Convenience sampling was utilized to collect data from a sample size of 112 respondents using questionnaires distributed via online platforms, including social media, messaging applications, and email. The findings revealed that only three features of an accounting information system were positively related to the performance of SMEs in Malaysia, namely accuracy, reliability, and ease of use. Therefore, an accounting system must generate accurate, reliable, and easy-to-use data to assist management in making informed decisions. Companies need to provide internal and external training for accountants and decision-makers and give organizational culture the attention it deserves as it impacts accounting data quality. This training should aim to promote a strong work ethic and a culture of excellence.